Documental audiovisual “Mujeres decididas”. - Chiriboga Naranjo, Eliana Gioconda (2016)
Gender-based violence against women, a problem that has been invisible throughout the years and affects women of all ages , fear to report or seek help lead them to shut up the abuse and live in fear and submerged aggression , they refuse to break the cycle of vio lence. At present, they have created laws that protect women from all forms of aggression, in addition to organizations that provide psychological support, so that from the creation of these instances women who have experienced abuse make the decision to go to them to break the chains of submission and live a quiet life. The Equity and Justice Centres are places of support for women who experience violence, whether physical, psychological, sexual or patrimonial, here therapies to improve self esteem and encourage them to develop as active bodies in society are provided. The documentary "Determined Women" , conceptualized gender violence statistics and allows this situation in our country and also shows evidence of three brave women who decide to seek help know love themselves and their life takes a new direction.